2016
DOI: 10.1186/s12889-016-2951-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of knowledge about tuberculosis: results from SANHANES I, a national, cross-sectional household survey in South Africa

Abstract: BackgroundSouth Africa is one of the 22 high tuberculosis burden countries that contribute 80 % of the global tuberculosis cases. Tuberculosis is infectious and due to its rapid and easy transmission route poses a threat to population health. Considering the importance of social and psychological factors in influencing health outcomes, appraising knowledge and awareness of tuberculosis, remain vital for effective tuberculosis control. The main aim of this study was to investigate the factors that predict knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
4
26
1
Order By: Relevance
“…Possible reasons for this finding include better media access to TB information [11]. Consistent with previous studies [8,11-14], this study found that men, higher education, higher wealth status, rural residence, and various sources of TB information, including family/friends, school/workplace, health care providers, Internet, radio, television and newspaper, were associated with higher TB knowledge scores. It is possible that among rural dwellers who were aware of TB, the ACSM community sensitization on TB treatment-seeking [18] contributed to better TB knowledge scores.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Possible reasons for this finding include better media access to TB information [11]. Consistent with previous studies [8,11-14], this study found that men, higher education, higher wealth status, rural residence, and various sources of TB information, including family/friends, school/workplace, health care providers, Internet, radio, television and newspaper, were associated with higher TB knowledge scores. It is possible that among rural dwellers who were aware of TB, the ACSM community sensitization on TB treatment-seeking [18] contributed to better TB knowledge scores.…”
Section: Discussionsupporting
confidence: 89%
“…Agho et al [12] found that higher wealth status, higher education, urban residence, and higher exposure to media sources were associated with having ever heard of TB. Factors associated with TB knowledge may include younger age [9,12], men [9,13], higher education [8], higher economic status [8,9], rural residence [12], and learning about TB from television, brochures, health workers, and teachers [14]. Factors negatively associated with TB courtesy stigma may include older age [7], men [15], higher wealth status [7], and TB knowledge [7].…”
Section: Introductionmentioning
confidence: 99%
“…We found good knowledge levels of TB transmission, cure and coexistence with HIV in the study. Elsewhere in a South African national community-based study[27], just as we found, almost three quarters were knowledgeable of TB. However, it is concerning that questions related to TB/HIV co-infections were the least correctly answered showing lower levels of HIV/TB integration awareness.…”
Section: Discussionsupporting
confidence: 52%
“…Community groups could also be established to discuss antibiotic stewardship and the impact of resistance, following principles developed in an urban township in Cape Town, in which patient adherence groups were found to be effective as a model of care. 68…”
Section: Discussionmentioning
confidence: 99%